2023
DOI: 10.3390/muscles2020011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondria in Mediation of Skeletal Muscle Repair

Abstract: Musculoskeletal health is directly linked to independence and longevity, but disease and aging impairs muscle mass and health. Complete repair after a pathological or physiological muscle injury is critical for maintaining muscle function, yet muscle repair is compromised after disuse, or in conditions such as metabolic diseases, cancer, and aging. Regeneration of damaged tissue is critically dependent upon achieving the optimal function of satellite cells (muscle stem cells, MSCs). MSC remodeling in muscle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 455 publications
0
4
0
Order By: Relevance
“…Muscle mitochondria play a critical role during skeletal muscle repair, as it requires a substantial energy supply, and mitochondria are the primary source of energy production. In this sense, satellite cell signaling, which is a key factor in muscle repair, can be regulated by the mitochondria ( Alway et al, 2023a ). Mitochondria have also been shown to be essential in the processes of myoblast differentiation and migration into damaged fibers since mitochondrial dynamics disorders are an impediment to correct myogenic differentiation ( Kim et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle mitochondria play a critical role during skeletal muscle repair, as it requires a substantial energy supply, and mitochondria are the primary source of energy production. In this sense, satellite cell signaling, which is a key factor in muscle repair, can be regulated by the mitochondria ( Alway et al, 2023a ). Mitochondria have also been shown to be essential in the processes of myoblast differentiation and migration into damaged fibers since mitochondrial dynamics disorders are an impediment to correct myogenic differentiation ( Kim et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The journal fosters discussion, facilitates cross-disciplinary collaboration, and contributes to the overall progression of myology knowledge. The most successful and cited papers of last year were on using astaxanthin for muscle pain biomarkers after eccentric exercise [1], clinical gamma sarcoglycan's socioeconomic impact [2], the role of mitochondria in muscle repair and longevity [3], and the use of muscle MRI in the diagnosis of limb-girdle syndromes [4].…”
Section: Impact and Significancementioning
confidence: 99%
“…Maintaining the quality of the mitochondrial network plays an important role in the development and functioning of muscle tissue. Indeed, pharmacological modulation of mitochondrial function has been shown to be useful in the treatment of induced and genetic myopathies and significantly improves muscle state and the quality of life of experimental animals [ 1 , 2 ]. Along with this, one of the discussed areas of modern biomedicine is mitochondrial transplantation therapy (MTT) based on the replacement of defective mitochondria with healthy ones.…”
Section: Introductionmentioning
confidence: 99%
“…It is hypothesized that additional mitochondria in regenerating muscles may increase the overall energy production required for protein assembly. In addition, MTT can enhance mitophagy (removal of defective organelles) or promote the introduction of mitochondrial DNA into the mitochondria of recipient cells [ 1 ]. It has also been shown that allogeneic mitochondria are found predominantly in the nucleus region of muscle cells, suggesting that they are optimally located for calcium buffering and prevent calcium overload of skeletal muscle fibers, as seen in cardiomyocytes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%